Exchange - Trade Funds (ETFs) and stock liquidity: Vietnamese evidences - Nguyen, Thi Minh Hue (ISERD International Conference, 2020)
The paper examnines how the introduction of Vietnamese ETFs impacts on liquidity of the underlying stocks. We found that the component stock’s liquidity decreased after the firt Vietnamese-based ETF (DBX) introduced in 2008, but significantly improved after the other two ETFs introduced in 2009 and 2014 (VNM and E1VFVN30, respectively). In addition, the stock liquidity change is more pronounced for the stock which had lower weight in the ETFs. The empirical findings may results in policy implication about the effects of ETF creation on the Vietnam stock market under different trends of stock market. ETF creation not only provides a new and alternative investment,, but also diversified and transparent investment tool to Vietnamese investor